Tibial plato leveling osteotomy - Tatarunas, Angelica Cecilia; Martinez, Steven A.; Matera, Julia Maria (Semina: Ciências Agrárias, 2008)
The tibial plateau leveling osteotomy (TPLO) is a relatively new and innovative surgical treatment for the cranial cruciate ligament rupture in the canine species. The real intent of the procedure is to provide functional stability to the stifle joint by eliminating or neutralizing the cranial tibial thrust during weight bearing instead to restore the cranial cruciate ligament function. The proposal of this study is to report a review of the TPLO procedure, emphasizing procedure, surgical technique, post operative care and complications. The TPLO procedure consists in a radial osteotomy in the tibial plato and rotation of the caudal plateau in order to obtain a desired angle. After the leveling of the tibial plateau, a bone plate and screws are used to stabilize the osteotomy until bone is healed up. The complications that have been associated with the procedure include tibial tuberosity fracture and patellar tendon tendinosis. This procedure has become increasingly more popular for surgical treatment of cranial cruciate ligament injuries in large breed dog. The long term clinical results have not been completely elucidated yet. It has been showed that this technique doesn't halt the degenerative joint disease.